2021
DOI: 10.1016/j.pnpbp.2020.110150
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization of psychiatric and justice-involved populations during the COVID-19 pandemic

Abstract: Psychiatric and justice-involved populations are known to be stigmatized and particularly vulnerable to adverse outcomes during COVID-19. The increased attention toward vulnerable populations from healthcare authorities, the media, and the general public has made it critical to uncover any developing stigmatization toward these groups and the possible consequences. The prioritization of public safety and shift in the prioritization of resource allocation and service delivery could lead to a rise in negative pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
(39 reference statements)
1
26
0
2
Order By: Relevance
“…Finally, treatment-related data revealed a sort of self-stigma given that many patients reported feelings of guilt or being undeserving of treatment in comparison to the need of physical healthcare due to the COVID-19 disease. This is in line with the internalized stigma seen in individuals with EDs [ 68 ] and with stigma-related data for other psychiatric conditions collected during the pandemic [ 69 ] and may contribute to worsen the renowned unmet treatment needs among people with EDs [ 70 ].…”
Section: Discussionsupporting
confidence: 74%
“…Finally, treatment-related data revealed a sort of self-stigma given that many patients reported feelings of guilt or being undeserving of treatment in comparison to the need of physical healthcare due to the COVID-19 disease. This is in line with the internalized stigma seen in individuals with EDs [ 68 ] and with stigma-related data for other psychiatric conditions collected during the pandemic [ 69 ] and may contribute to worsen the renowned unmet treatment needs among people with EDs [ 70 ].…”
Section: Discussionsupporting
confidence: 74%
“…The majority of papers were opinion pieces, with the exception of 10 case studies, [30][31][32][33][34][35][36][37][38][39] seven guidelines, 13-16 40-42 six literature reviews, [43][44][45][46][47][48] five qualitative studies, [49][50][51][52][53] three cross-sectional studies, [54][55][56] three briefings, [57][58][59] three case studies 37 39 60 and one study protocol. 61 All assessed studies were found to be of poor quality (see online supplemental appendix 3).…”
Section: Resultsmentioning
confidence: 99%
“…Dies gemahnt im Hinblick auf die Sicherung der Behandlungsqualität und die Wahrung der Interessen und Rechte dieser auch in der psychiatrischen Fachwelt marginalisierten und stigmatisierten Patientengruppe zu besonderer Wachsamkeit und Vorsicht. Infolge einer rezessionsbedingten Verknappung wirtschaftlicher Ressourcen, die für Erhaltung und Ausbau öffentlich finanzierter forensisch-therapeutischer Behandlungseinrichtungen bereitgestellt werden, ist zu befürchten, dass in der Öffentlichkeit die „Sicherung“ psychisch erkrankter Rechtsbrecher gegenüber Behandlungsaufträgen an Gewicht gewinnen könnte [ 1 ]. Andererseits stellt eine zunehmende Nutzung digitaler Kommunikationsmittel im forensischen Kontext eine besondere Herausforderung dar.…”
Section: Hintergrundunclassified